Nursing Care for Mrs. S (P₂A₀) Post Sectio Caesarea Day First Due to Prolonged Labor Indication at Marjan Bawah Room, RSUD dr. Slamet Garut - Permana, Gin Gin Sugih; Daniati, Eva (Nursing Case Insight Journal, 2024)
This study discusses the nursing care provided to Mrs. S (P₂A₀) who underwent a Caesarean section on the day of surgery due to prolonged labor. Based on medical records from RSUD dr. Slamet Garut from January to May 2024, there were 908 cases of Caesarean sections, with prolonged labor accounting for 254 cases or 27.97%. The purpose of this case study was to provide direct and comprehensive nursing care for Mrs. S, addressing acute pain, physical mobility impairment, infection risk, self-care deficit, ineffective breastfeeding, and grief. The study employed a descriptive case study method. Interventions included pain management, mobilization support, wound care, self-care support, breastfeeding education, and grief support. The evaluation revealed partial resolution of acute pain, physical mobility issues, infection risk, and ineffective breastfeeding, while the grief diagnosis remained unresolved. The study concludes that the nursing care process was well-executed and documented, and recommends collaboration between nurses, patients, and families to prevent complications in postoperative care.